2013
DOI: 10.33588/rn.5705.2013174
|View full text |Cite
|
Sign up to set email alerts
|

Fracturas en la atrofia muscular espinal

Abstract: Patients and methods. Sixty-five patients with spinal muscular atrophy were studied. Cases of fractures diagnosed by means of X-rays were collected and the following parameters were analysed: type of spinal muscular atrophy, gait, age at the time the fracture occurred, mechanism of production, location, treatment applied and functional repercussion. Results. Thirteen patients (20%) presented a total of 20 fractures (four of them presented two or more fractures). The mean age was 6.35 years. The fractures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…Children with SMA have a high incidence of fragility fractures. But only 5% (2/40) of children with SMA in our study had fractures, which was significantly lower than the fracture rate of 36-46% reported by other studies [22,30,31]. The low rate of fractures in our study patients may be related to their decreased participation in outdoor activities and rehabilitation.…”
Section: Discussioncontrasting
confidence: 76%
“…Children with SMA have a high incidence of fragility fractures. But only 5% (2/40) of children with SMA in our study had fractures, which was significantly lower than the fracture rate of 36-46% reported by other studies [22,30,31]. The low rate of fractures in our study patients may be related to their decreased participation in outdoor activities and rehabilitation.…”
Section: Discussioncontrasting
confidence: 76%